Pemberdayaan Warga Binaan Balai Pemasyarakat (Bapas) Kelas 1 Kota Malang Melalui Pelatihan Pengolahan Kopi Lokal Menjadi Produk Kekinian - Sugiri, Wiku Aji; Priatmoko, Sigit; Sudarmawan, Barianto Nurasri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
One of the social reintegration efforts for clients or assisted residents of the Class I Penitentiary of Malang City is economic empowerment. This effort aims to make the inmates have economic independence and are able to interact socially again in the community. This empowerment activity is carried out in the form of providing training on processing coffee beans into contemporary products to support these efforts. The research team used the Participatory Action Research (PAR) method with four stages, namely planning (plan), implementation (action), observation (observe), and reflection (reflect). Analysis of the results of the activities shows that in general, the training activities that have been carried out have not fully resolved the problems faced by the assisted communities. This shows that some of the activity targets that have been set have not yet been achieved. In order to achieve of these targets requires the support of universities that oversee the implementation of the service program. However, the two target activities that have been set have been well achieved, namely increasing the skills of participants in processing coffee and opening up participants' insights about the coffee business/business as well as the opportunities and challenges in the Greater Malang area. Considering the expectations of the assisted communities who want sustainable assistance until a joint business is formed. Therefore, UIN Maulana Malik Ibrahim Malang together with the Class 1 Penitentiary of Malang City needs to strengthen cooperation and design further mentoring programs for the inmates.